Assessment of psychiatric morbidity among health-care students in a teaching hospital, Telangana state: A cross-sectional questionnaire-based study - Udai Kiran; Madhavi Padma; K. V. N. R. Pratap; Siva Kalyan; Parlapalli Vineela; Surya Chandra Varma (Wolters Kluwer Medknow Publications, 2017)
Introduction: Professional education can be a stressful experience for health-care students and may impact negatively on emotional well-being and academic performance which leads to psychiatric morbidity. The aim of this study is to assess the prevalence of psychiatric morbidity among the professional health-care students. Materials and Methods: A cross-sectional study was conducted among professional health-care students in a tertiary care teaching hospital of Telangana state. The information regarding demographic data, academic achievements, and positive and negative events in the recent past was collected using semi-structured pro forma, and the General Health Questionnaire (GHQ)-28 is used to assess the psychiatric morbidity. Descriptive analysis and Pearson's correlation analysis were done to analyze the data. Results: A total of 836 students participated in the study, and the overall mean GHQ total score in the study population was 26.8, which is above the cutoff (24) score. The prevalence of psychiatric morbidity among study population is about 58.7%. Academic achievement and negative events in the recent past had effect on psychological morbidity and showed high GHQ scores among study population which was found to be statistically significant. Conclusion: The poor academic performance and negative events had a strong impact on psychological morbidity of students. The higher level of psychological morbidity warrants need for intervention such as social and psychological support to improve the quality of life for the health-care students. Further, a creation of positive academic environment as a teamwork of faculty, administration, educational experts, and students helps to develop psychological healthy dental and medical professionals who can perform better in a coming future.